Спектрофотометричний метод дослідження аценокумаролу - Гречана, Олена Володимирівна; Сербін, А. Г.; Буряк, Валерій Прокопович; Grechana, O. V.; Serbin, A. G.; Buriak, V. P. (My University, 2017)
Серцево-судинні захворювання, а саме системна емболія та кардіоемболічний інсульт, є найчастішою причиною летальності серед людей. В останні роки у кардіології зростає застосування пероральних антикоагулянтів, зокрема аценокумаролу. Незважаючи на застосування даного препарату в терапевтичній практиці, його фізико-хімічні властивості вивчені недостатньо. Під час дослідження нами були вивчені УФ-спектри аценокумаролу в розчинниках різної полярності, встановлена природа смуг поглинання, виявлена фізіологічно активна частина молекули (фармакофор), а на підставі розрахунку основних оптичних характеристик електронних спектрів поглинання досліджуваної речовини визначені дозволеність та вірогідність переходу електронів у його молекулі. Cardiovascular diseases, namely auricle’s fibrillation, are the most frequent source of a system embolism and a cardioemboly stroke. Among 4-oxybenzopyrone’s derivatives, which are the doctors prescribed to the patient with the specified etiology of heart diseases and cardiovascular system, is rather often recommended an acenocoumarol. This medicine as anticoagulant has an indirect action and reduces risk of a stroke and its consequences approximately on two thirds. In recently years the scientists pay appreciable attention to search of new original domestic drugs which can be applied to prevention of a cardiovascular system’s embolism of the person. Development of new medicines for researching in cardiology for the purpose of decrease of embolic stroke consequences and following treatment of the residual phenomena of this disease is impossible without detailed and careful studying of UF-ranges of derivatives 4-oxybenzopyrones drugs. Nowadays the possibilities of UF-spectrophotometery allow to establish structure of again synthesized bond, dependence between structure and effect of medicines and to identify the part of a molecule which causes its pharmacological action (pharmakophore).
The investigation of acenocoumarol by spectrophotometric мethod
Keywords: 4-оксикумарин; аценокумарол; УФ-спектри; фармакофор; переходи електронів; 4-oxycoumarin; acenocoumarol; UV spectra; pharmacophore; electron relocation